On the Restoration of the Chronology of Pontic Olbia 4th – 1st Centuries BC - Mykola Nikolaev (Cercetări Arheologice)
The history of studying the most important lapidary inscription of Olbia, the catalogue of eponyms IOSPE I2 201, is considered. The current state of research on this remarkable monument is shown selectively compared with monuments of lapidary, magical, ceramic, and numismatic epigraphy.